PCNN - Firefly Based Segmentation and Analysis of Brain MRI - Thamaraichelvi, B (International Journal of Computer Sciences and Engineering, 2020)
In this proposed method, the segmentation of brain Magnetic Resonance Images (MRI) has been carried out using Pulse Coupled Neural network (PCNN) and classification by Back Propogation Neural Network (BPNN) techniques. The proposed method includes five stages pre-processing, clustering, feature extraction, feature selection and classification. For extracting the features Non Sub-sampled Contourlet Transform (NSCT) method has been used. For feature selection optimized Fire-fly intelligence has been preferred. Finally, the selected features are given to BPNN to identify the input data either as normal or abnormal. The performance of the classifier was evaluated in terms of True Positive (TP), True Negative (TN), False Positive (FP), False Negative (FN) and the accuracy was found to be good.